Multiphysikalische Betrachtung von Kabeln und Leitungen unter mechanisch-dynamischer Belastung - Ehlenz, Tobias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
As part of a cooperative doctorate between the Friedrich-Alexander University of Erlangen Nuremberg and the University of Applied Sciences Trier, cables and transmission lines that users primarily perceive as electrical components have been researched similar to the established failure and dimensioning scheme of a machine element. The current work deals with the investigation of mechanically stressed cables and lines. Their use should get more reliable and the point of time for exchange of permanently moved lines be optimized. Cables in moving applications have highly complex electrical and mechanical requirements that are currently under-researched or insufficiently standardized. As it is common with other machine elements, operating time cannot be calculated. Especially with regard to Industry 4.0, unscheduled machine downtimes could become critical. With accelerated aging tests, manufacturers and users try to test their products in an increasingly shorter time-to-market. They use the alternating bending test, described in DIN EN 50396 to verify the cables’ conformance. The research shows that the requirements of the standard are insufficiently described. After improvements of the test operations, which focused on the reproducibility, the alternating bending test defines the starting point of the multiphysical lifetime tests. Based on the findings of the parameter studies, a proposed standard for improving the test standard DIN EN 50396 was submitted to the responsible parent body. With the multiphysical recording of the course of damage during endurance tests, relevant wear patterns for moving lines can be identified. They form a novel phase model of the service life of mechanically dynamic loaded cables. The investigations show that structural changes and surface roughness of the copper material occur under prolonged mechanical stress before fracturing of the probands. Changes in the edge regions of the electrical material can be measured, making use of the skin effect. In conductors that are carrying high-frequency currents, the current density concentrates at the peripheric region of the conductor. An incipient roughness of the conductor leads to a change in the attenuation of a signal to be transmitted. In the run-up to empirical experiments, corresponding electrodynamical simulations on modelled conductors confirm the assumption. They show the increased current density at the peripheric area of a correspondingly aged, rough conductor. In subsequent empirical tests, an exchange time of test lines can be detected with insitu high-frequency attenuation measurement. The high-frequency measurement is a nondestructive, in-situ diagnostic option for mechanical cable wear. The measurement method is suitable for the commercial use of a later cable monitoring system, in which lines can be evaluated during their operation with regard to estimated remaining lifetime. The research results contribute to a predictable product life of the mechanically loaded electrical lines and thus to increased reliability in many industries. <br
Keywords: Cable; Multiphysics; Aging